Neolithic and medieval settlements on Debela šuma (Đakovo) site: Possibilities for presentation - Miloglav, Ina (Array, 2008)
During 2006 and 2007 mayor rescue excavations were conducted on the Croatian part of the Vc motorway (Budapest-Ploče). This poster presents preliminary results of the site Debela šuma in the vicinity of Đakovo from late Neolithic and medieval period. On the site remains of the settlements with infrastructure were recovered. These two periods are represented in more or less equal proportions on the investigated surface. Through horizontal distribution different settlement patterns during Neolithic and Middle Ages are clearly observed. While during Neolithic, vast majority of the settlement area is concentrated on the slight elevation, during Middle Ages, in the lower part, closer to the stream. Both populations were obviously using the same water source, which was probably the reason for inhabitation of this particular area. On this poster, excavated area will be present with aerial photography, 3D relief model, and ortophoto. On those maps, detailed ground plan processed in AutoCad with all the features is included.